2015
DOI: 10.1002/jeab.157
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐state choice between four alternatives obeys the constant‐ratio rule

Abstract: We investigated why violations to the constant-ratio rule, an assumption of the generalized matching law, occur in procedures that arrange frequent changes to reinforcer ratios. Our investigation produced steady-state data and compared them with data from equivalent, frequently changing procedures. Six pigeons responded in a four-alternative concurrent-schedule experiment with an arranged reinforcer-rate ratio of 27:9:3:1. The same four variable-interval schedules were used in every condition, for 50 sessions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 30 publications
5
18
2
Order By: Relevance
“…The present experiment found no convincing evidence that the birds showed preference pulses in any of the two‐ or three‐alternative conditions; the birds tended not to stay on the just reinforced key. This finding supports Bensemann et al’s () study, which also found no strong evidence for preference pulses. The birds’ preference in the present experiment following a reinforcer was nearly always for the richest alternative.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The present experiment found no convincing evidence that the birds showed preference pulses in any of the two‐ or three‐alternative conditions; the birds tended not to stay on the just reinforced key. This finding supports Bensemann et al’s () study, which also found no strong evidence for preference pulses. The birds’ preference in the present experiment following a reinforcer was nearly always for the richest alternative.…”
Section: Discussionsupporting
confidence: 90%
“…Yet, Jensen's model was able to mathematically describe all of the birds’ data equally well, would it be possible for one model to conceptually describe contradictory data like this? Would the same model conceptually consolidate the findings of Davison et al (), Elliffe and Davison (), and Bensemann et al (), as well as the contradictory findings of the present experiment, and the findings of Beeby and Alsop ()? Mathematically, Jensen's model is a step towards “completing” the GML, but conceptually it is difficult to see how one model could untangle the variety of results from multiple‐alternative choice experiments.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations